DDRE-33. MOLECULAR DIFFERENTIATION OF IMIPRIDONES ONC201 AND ONC206. (9th November 2020) - Prabhu, Varun; Cuoco, Caroline; Jung, Jinkyu; Morrow, Sara; Kawakibi, Abed Rahman; Willette, Blair; Day, Marilyn; Anantharaman, Lakshmi; Charter, Neil; Rucker, Joseph; Doranz, Benjamin; Basken, Joel; et al.
Abstract: ONC201 is the first bitopic antagonist of dopamine receptor D2 (DRD2) and agonist of ClpP in oncology. In clinical trials, the small molecule has induced durable tumor regressions and clinical benefit in H3 K27M-mutant glioma patients while being well tolerated. ONC206 is a chemical derivative of ONC201 with nanomolar anti-cancer potency. In this study, we describe receptor pharmacology, gene expression profiling, acquired resistance and biodistribution studies that suggest ONC206 exhibits distinct therapeutic properties relative to ONC201. ONC206 exhibited a nanomolar Ki for DRD2 with complete specificity across human GPCRs and complete DRD2 antagonism. Schild analyses of ONC206 in cAMP and β-Arrestin recruitment assays revealed hallmarks of non-competitive DRD2 antagonism, unlike antipsychotics but similar to ONC201. Shotgun mutagenesis across DRD2 identified 7 residues critical for ONC206-mediated antagonism at orthosteric and allosteric sites. Six residues were critical for ONC201 and ONC206, however the impact varied between the two compounds and one allosteric residue was exclusive to ONC206. Structural mapping revealed that some ONC206-critical allosteric residue interactions are located at the interface of TM-IV and –V that mediates the DRD2 homodimer interface. Gene expression profiling revealed ONC206 and ONC201 induce distinct signatures in U87 glioblastoma cells, further supporting distinct functional effects. Similarly, T98G glioblastoma cells with acquired resistance to ONC201 or ONC206 reveal partial cross resistance. Finally, rat biodistribution studies revealed nanomolar CSF concentrations that exceed therapeutic thresholds, unlike ONC201. In summary, ONC206 exhibits increased non-competitive DRD2 antagonism, nanomolar potency, distinct biodistribution, differentiated gene expression and disruption of DRD2 dimers relative to ONC201. Thus, ONC206 may be uniquely poised to address tumors that are not addressed by ONC201 or have developed acquired resistance.